Proposed model and strategy for Indonesian higher education facing technological disruption and Industrial Revolution 4.0 using Newton's Laws analogy - Erkata Yandri; Sparisoma Viridi; Rizal F. Hariadi (Universitas Mercu Buana, 2023)
All economic sectors in the world cannot be separated from the challenges of facing an era of technological disruption and the Industrial Revolution 4.0 (TD4IR). As centers of higher education, campuses also cannot escape from this difficult situation. Many studies have discussed the impact of TD4IR on higher education, unfortunately, without a detailed strategy for dealing with it. The global issues were analyzed using a physical approach, such as Newton's laws. Our study's purpose is to evaluate a strategic principle that Indonesian colleges can use to prepare for TD4IR. We applied Newton's analogy system to strategic management, then modeled with the derivation of the formula, followed by modeling with the simulation, to determine the changes that higher education would need to make in response to Industrial Revolution 4.0. Acceleration and deceleration scenarios are implemented with a square or cube increase or reduction. From the modeling, the parameters of Newton's laws, such as mass, friction (barriers to change), force (internal assets as a driving force), etc., must be properly matched to the idea of strategic management of higher education to give a clear picture of the problems. From the simulation, higher education needs to know the minimum value of its organizational system so it can figure out what needs to be done right away. The organization doesn't suddenly slow down or stop; higher education needs to speed up as much as possible.